Peningkatan Hasil Belajar Pengukuran Panjang Melalui Model Pembelajaran Cooperative Learning Tipe Make A Match Pada Siswa Sekolah Dasar - Reni Sri Mulyani; Iis Nurasiah; Irna Khaleda Nurmeta (FKIP, Universitas Palangka Raya, 2024)
Education must function to realize and develop the various potentials that exist in humans in the context of diversity, morality, individuality/personality, sociality and culture as a whole and integrated. In short, education serves to humanize humans. The current educational paradigm requires teachers to improve the quality of learning, so the selection of learning models is really necessary so that learning in class is active and fun. One of the models used is cooperative make a match type. The advantage of this technique is that students find partners while learning about a concept or topic. , in a pleasant atmosphere and leading to active student learning in order to facilitate the learning that students do in the Mathematics subject, the material for Length Measurement has problems and obstacles so that the acquisition of student learning outcomes is very low. The purpose of this learning improvement research was to find out the increase in student learning outcomes by using the Make a Match type cooperative learning model in the Length Measurement material in class II (Two) students at Pasekon State Elementary School, Surade District, Sukabumi Regency with a total of 19 students, consisting of 14 men and 5 women.